The Influence of Pharmacological Preconditioning with Sevoflurane on Incidence of Early Allograft Dysfunction in Liver Transplant Recipients - Andrei F. Minou; Alexander M. Dzyadzko; Aliaksei E. Shcherba; Oleg O. Rummo (Anesthesiology Research and Practice)
Background. Pharmacological preconditioning is one of the tools used to diminish preservation injury. We investigated the influence of sevoflurane preconditioning of liver grafts on postoperative graft function. Methods. Consecutive 60 deceased brain donors were randomized into sevoflurane group or control group. In sevoflurane group donors were treated with endexpiratory 2,0 volume% of sevoflurane during procurement. Primary endpoint was postoperative liver injury. Secondary endpoint was incidence of early allograft dysfunction (EAD). Results. The groups were not different in median DRI, donor age, graft steatosis, and MELD score. Peak AST and ALT levels were lower in sevoflurane group than in control group: 792 and 1861 (𝑃=0,038) for AST and 606 and 1191 for ALT (𝑃=0,117). Incidence of EAD was 16,7% in sevoflurane group and 50% in control group (Fisher test, 𝑃=0,013). In subgroups without steatosis preconditioning with sevoflurane did not have influence on incidence of EAD. In subgroups with mild and moderate steatosis incidence of EAD was lower in recipients of liver grafts treated with sevoflurane. Conclusions. Preconditioning with sevoflurane during organ procurement improves graft function by lowering incidence of early allograft dysfunction, particularly in recipients of steatotic liver grafts.